2020
DOI: 10.1016/j.pec.2020.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with parental concerns: A study of GPs' practice

Abstract: Objective: To investigate patterns of GPs' exploration and termination of dialogues about parental concerns in preventive child health assessments. Methods: Interactional microanalysis of video recordings of 32 preventive child health assessments using conversation analysis. Results: The GPs asked parents about concerns, but most concerns disclosed by parents were still left unexplored at the end of the consultation. Termination of dialogues about concerns could be achieved effectively by GPs through letting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Clinicians’ ability to listen and communicate is an important element in patient experience [ 44 , 47 ], and trustful clinician-patient relationships along with positive responsiveness should enable parents to bring up psychosocial problems in the future. It has previously been identified that parental concerns mentioned during the developmental assessments were not subsequently explored and were often terminated by the clinician [ 48 ]. Moreover, psychosocial issues were repeatedly de-emphasised in favour of the physical examination [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians’ ability to listen and communicate is an important element in patient experience [ 44 , 47 ], and trustful clinician-patient relationships along with positive responsiveness should enable parents to bring up psychosocial problems in the future. It has previously been identified that parental concerns mentioned during the developmental assessments were not subsequently explored and were often terminated by the clinician [ 48 ]. Moreover, psychosocial issues were repeatedly de-emphasised in favour of the physical examination [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been identified that parental concerns mentioned during the developmental assessments were not subsequently explored and were often terminated by the clinician [ 48 ]. Moreover, psychosocial issues were repeatedly de-emphasised in favour of the physical examination [ 48 ]. This demonstrates that uncovering psychosocial aspects is not equivalent to handling psychosocial concerns properly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is critical, since children exposed to environmental stressors or early adverse life events might have a higher risk of cognitive, emotional, and health problems 31 . These concerns are often not addressed during general practice consultations due to time limitation or reluctancy 64 . This leads to discrepancy between concern and elaboration 64 .…”
Section: Musculoskeletal Pain In General Practicementioning
confidence: 99%
“…These concerns are often not addressed during general practice consultations due to time limitation or reluctancy 64 . This leads to discrepancy between concern and elaboration 64 . Identifying and addressing negative pain beliefs becomes important in treating adolescents with MSK pain in general practice 65 to encourage acceptance and transition into self-management.…”
Section: Musculoskeletal Pain In General Practicementioning
confidence: 99%